Association of pan-immune inflammation value, platelet-to-neutrophil ratio and fibrinogen-to-albumin ratio with lower extremity artery disease in patients with type 2 diabetes mellitus: a cross-sectional study - Zeng, Sheng; Ou, Bin; Liu, Zhiyuan; Shi, Feng (Frontiers in Endocrinology, 2026)
BackgroundInflammation and coagulation function are considered to be related to atherosclerotic diseases. However, the relationship between comprehensive indices reflecting inflammatory and procoagulant statuses(pan-immune inflammation value (PIV), platelet-to-neutrophil ratio (PNR), and fibrinogen-to-albumin ratio (FAR)) and lower extremity artery disease(LEAD) in patients with type 2 diabetes mellitus (T2DM) is unclear. This research is precisely aimed at studying this issue.MethodsA total of 9043 patients with T2DM were retrospectively analyzed. PIV, PNR, and FAR were calculated based on monocyte count, neutrophil count, platelet count, lymphocyte count, fibrinogen, and albumin. The relationship between PIV, PNR, and FAR and LEAD was analyzed.ResultsThere were 2573 (28.5%) T2DM patients with LEAD and 6470 (71.5%) cases without. The optimal threshold of PIV, PNR, and FAR was 515.86, 43.145, and 0.105 by ROC analysis. There were statistically significant differences in proportions of high PIV, low PNR, and high FAR between T2DM patients with and without LEAD. Logistic regression analysis showed that cigarette smoking(odds ratio(OR): 1.802, 95% confidence interval(CI): 1.506-2.156, p < 0.001), hypertension (OR: 1.633, 95% CI: 1.460-1.826, p < 0.001), history of cerebrovascular disease (OR: 3.034, 95% CI: 2.678-3.437, p < 0.001), and diabetic peripheral neuropathy (OR: 18.983, 95% CI: 15.819-22.780, p < 0.001), high PIV (OR: 1.338, 95% CI: 1.181-1.515, p < 0.001), low PNR (OR: 2.234, 95% CI: 1.985-2.515, p < 0.001), and high FAR (OR: 1.676, 95% CI: 1.493-1.881, p < 0.001) were significantly associated with LEAD in T2DM patients.ConclusionsPIV, PNR, and FAR can serve as potential inflammation- and coagulation-related biomarkers for assessing the risk of LEAD in T2DM patients, thereby providing a reference basis for clinical early screening, risk stratification, and intervention.